Feedback Control of Flow Separation Using Plasma Actuator and FBG Sensor. (14th December 2016) - Segawa, Takehiko; Suzuki, Daiki; Fujino, Takayasu; Jukes, Timothy; Matsunuma, Takayuki
Abstract : A feedback control system for mitigating flow separation was developed by using a string-type dielectric-barrier-discharge (DBD) plasma actuator and a fiber Bragg grating (FBG) sensor. Tangential jets were induced from the string-type DBD plasma actuator, which was located at 5% chord from the leading edge of an NACA0024 airfoil. The FBG sensor was attached to the interior surface near the root of the cantilever beam modeled on the pressure surface of the airfoil. The strain at the cantilever root was reflected in the form of Bragg wavelengths (λ B ) detected by the FBG sensor when the cantilever tip was vibrated by the flow near the trailing edge of the airfoil. It was found that calculating running standard deviations in the Bragg wavelength (λ B ′ ) detected by the sensor was valuable for judging flow separation in real time. The feedback control of flow separation on the NACA0024 airfoil was successfully demonstrated by setting λ B ′ = 0.0028 with periodic flow separations generated in a wind tunnel by oscillating a side wall of the test section with frequency f w = 0.42 Hz. It was confirmed that the appearance probability of flow separation tends to decrease with a decrease in the duration for calculating λ B ′ and with an increase in the duration of jet injection.